Cryptic species, taxonomic inflation, or a bit of both? New species phenomenon in Sri Lanka as suggested by a phylogeny of dwarf geckos (Reptilia, Squamata, Gekkonidae, Cnemaspis). Issue 5 (3rd September 2017) - Agarwal, Ishan; Biswas, Sayantan; Bauer, Aaron M.; Greenbaum, Eli; Jackman, Todd R.; Silva, Anslem De; Batuwita, Sudesh
Abstract : We evaluated the status of 16 of 22 recognized Sri Lankan Cnemaspis Strauch species, and flagged overlooked diversity with two mitochondrial (cyt b & ND2) and two nuclear markers (RAG1 & PDC) totalling 2829 base pairs. A fossil-calibrated timetree and sampling of other South Asian Cnemaspis provide insights into the diversification of the genus in peninsular India and Sri Lanka. Phylogenetic analyses consistently inferred two broad clades within South Asian Cnemaspis, with Sri Lankan species in two clades, which we call the podihuna and kandiana clades. Each Sri Lankan clade as a whole is sister to Indian taxa and nested within Indian lineages. Cnemaspis modigliani Das from Indonesia is a member of the kandiana clade. This suggests a minimum of two dispersal events between India and Sri Lanka and one between Sri Lanka/India and South-east Asia. South Asian Cnemaspis date back to at least the Eocene, in Sri Lanka to the early Miocene, with late Miocene diversification in the kandiana clade. All but one of the named species we sampled is likely to be valid, and 10 divergent unnamed lineages may warrant specific recognition. A resolution of Sri Lankan Cnemaspis taxonomy will require thorough sampling and the use of both morphological and molecular data.